External cost as an indicator for sustainable electricity generation system - Matsuki, Y.; Brondzia, О.; Maslukivska, O. (Системні дослідження та інформаційні технології, 2010)
This research applies the Impact Pathway Approach [1] for identifying the external cost for the fossil-fuel electricity production in Ukraine. Using the SimPact Computer Code and Willingness to Pay survey, it calculates the external costs of the morbidity and mortality of population due to the air pollutants emitted from an electricity generation plant using as an example Triypilska Electric Power Generation Plant in Ukrainka town. Based on the research results there were made recommendations to include the external costs into the price of electricity in Ukraine generated from the fossil fuel combustion. Застосовано підхід шляху впливу (Impact Pathway Approach) для визначення зовнішніх витрат виробництва електроенергії з викопних джерел в Україні. За допомогою комп’ютерної програми SimPact та методики опитування щодо бажання платити обраховано вартість зовнішніх витрат від впливу викидів теплоелектростанції на захворюваність та смертність населення на прикладі Трипільської ТЕС у м. Українка. На основі отриманих результатів було зроблено рекомендації щодо включення вартості зовнішніх ефектів до ціни електроенергії в Україні, отриманої за допомогою спалювання викопних енергоносіїв. Использован подход пути влияния (Impact Pathway Approach) для определения внешних издержек производства электроэнергии из ископаемых энергоресурсов в Украине. При помощи компьютерной модели SimPact и методики опроса желания платить были исчислены внешние издержки от влияния выбросов теплоэлектростанции на заболеваемость и смертность населения на примере Трипильской ТЭС в г. Украинка. На основе полученных результатов были сделаны рекомендации о внесении стоимости внешних издержек в цену электроэнергии в Украине, полученную в результате сжигания ископаемых энергоносителей.